Pranata Hukum Perbankan Syari’ah Dalam Sistem Perbankan Nasional di Indonesia - Asep Maman (JOURNAL EKONOMI, KEUANGAN, PERBANKAN DAN AKUNTANSI SYARIAH, 2022)
The development of Islamic banks as part of the Islamic economic system in Indonesia can be said to be late compared to other countries where the majority of the population is Muslim. However, the sharia banking legal system is strong and parallel to other conventional banking. If there is a dispute resolution problem for Islamic banks according to the Constitutional Court Decision Number 93/PUU-X/2012, they can use 2 (two) channels, namely litigation and non-litigation. The litigation route for resolving disputes over sharia banks is the absolute authority of the religious courts, while the non-litigation path of the parties can make choices not only as specified in the Elucidation of Article 55 paragraph (2) of Law Number 21 of 2008 concerning Sharia Banking but can also take alternative others in accordance with the agreed contract. Supervision of the implementation of Sharia Banking, apart from being carried out internally, is also carried out by independent supervisory institutions, namely the Sharia Supervisory Board (DPS) and the National Sharia Council (DSN) which have the task of maintaining sharia banking towards an ideal situation and protect the Muslims. In addition, as a form of public participation, all Muslims have an obligation to supervise both directly and indirectly as a vehicle for admonishing ma'ruf nahi munkar to the implementation of sharia banking as the lifeblood of the Islamic economy.